Effects of elicitors from culture filtrate of Fusarium solani CL105 on flavonoid production of Scutellaria baicalensis calli - Cui, Xiaoxuan; Zhang, Xin; Sun, Huigai; Zheng, Yuguang; Su, Chunyan (Frontiers in Plant Science, 2024)
Endophytic fungi can promote secondary metabolite accumulation in medicinal plants. Previously, we observed that the culture filtrate of Fusarium solani CL105 promoted flavonoid production in Scutellaria baicalensis calli. However, the active ingredients and mechanisms associated with this secondary metabolite accumulation remain unclear. This study evaluates the effects and the underlying mechanism of different elicitors from the culture filtrate of F. solani CL105 namely, exopolysaccharide (EPS), exoprotein (EP), and other parts (OP), on the flavonoid production in S. baicalensis calli. The results indicated a significant increase in flavonoid production in S. baicalensis calli following treatment with EPS. Baicalin (1.40 fold), wogonoside (1.91 fold), and wogonin (2.76 fold) were most significantly up-regulated compared with the control. Transcriptome analysis further revealed up-regulation of key enzyme genes (CHS, CHI, FNS, and F6H) involved in flavonoid synthesis after 5 days of EPS treatment. Moreover, the expression of GA2ox and CYP707A-genes involved in gibberellin acid (GA) and abscisic acid biosynthesis (ABA), respectively-were significantly up-regulated. The expression levels of certain transcription factors, including MYB3, MYB8, and MYB13, were also significantly higher than in controls. Our results indicated that EPS was a main active elicitor involved in promoting flavonoid production in S. baicalensis calli. We postulated that EPS might stimulate the expression of MYB3, MYB8, MYB13, GA2ox, and CYP707A, leading to markedly upregulated CHS, CHI, FNS, and F6H expression levels, ultimately promoting flavonoid synthesis. This study provides a novel avenue for large-scale in vitro production of flavonoids in S. baicalensis.